Perubahan Luasan Mangrove Pesisir Timur Kabupaten Bangka Tengah Menggunakan Citra Satelit ASTER - Navisa Savira; Agus Hartoko; Wahyu Adi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Mangrove resources provide economic and ecological value. The expansion of residential areas makes the level of need for shelter as well as the region increases. This will have an impact on the utilization of mangrove in sufficient needs such as firewood, charcoal and building materials. If continue berlasngsung then do not deny the existence of mangrove degradation. The occurrence of mangrove degradation will have a direct impact on the local community. Considering the importance of mangrove function and the need for data of mangrove area change, it is needed to analyze the change of mangrove area in coastal of Bangka Tengah, which will be analyzed within 15 years in 2002 and 2017, so that the result of this study is expected to be further management by local government to conserve mangrove forests. This research was conducted from December 2017 to March 2018 with location station determination based on unsupervised image classification, that is classification based on digital number using RGB_231 image composite for ASTER image. Based on the results of the study, there is a change of mangrove area from 2002-2014 as much as 176.3 Ha or about 15.95% and in 2014-2017 there is an increase of 36.23 Ha or about 3.9%. The value of NDVI analys in East Coast of Central Bangka Regency in 2017 ranges from 0.005 to 0.156. the occurrence of the reduction of mangrove area due to the changing function of mangrove land into settlement, mangrove logging in the utilization of charcoal and mining industry. The addition of the extent of the addition of seedlings along the coast of Kurau and Penyak.